Self-control and Problematic Social Media Use: A Meta-Analysis - Zeynep Simsir-Gokalp; Muhammet Ibrahim Akyurek (Journal of Education in Science, Environment and Health)
Failure to exercise self-control is one of the leading causes of substance and behavioral addictions. Problematic social media usage (PSMU), a type of behavioral addiction, has become an increasingly serious problem with a significant impact on the lives of individuals of all generations. Therefore, it is crucial to understand the underlying mechanism of PSMU to effectively address the issue. This study performed a meta-analysis, which systematically synthesized existing research in the field, to establish the current empirical state of the relationship between self-control and PSMU. The study included 57 independent samples that met the inclusion and exclusion criteria (N = 29.576). The analysis results indicated a moderate negative association between self-control and PSMU (r = -.29). Furthermore, the moderator analysis outcomes suggested that the association between self-control and PSMU did not differ significantly based on variables such as developmental period, educational stage, geographic region, and publication status. The study’s findings are expected to inspire future investigations and therapeutic approaches.